Mulberry fruit polysaccharides alleviate diethylnitrosamine/phenobarbital-induced hepatocarcinogenesis in vivo: the roles of cell apoptosis and inflammation. Issue 2 (20th December 2021) - Li, Shanshan; Li, Yang; Sun, Hongjian; Jiang, Yang; Pan, Keming; Su, Yue; Bu, Nan
ABSTRACT: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors worldwide, and chemoprevention represents a feasible treatment to reduce the mortality of this carcinoma. Mulberry fruit polysaccharides (MFP) possess immunoregulatory and anti-inflammatory effects, which have been reported to alleviate liver damage evoked by CCl4 or alcohol in previous reports. However, its chemopreventive effect against liver carcinogenesis is insufficient. The present study was aimed to investigate the possible role of MFP as a pro-apoptosis, and anti-inflammatory agent to possess its chemoprevention property. Hepatocarcinogenesis was induced by diethylnitrosamine/phenobarbital (DEN/PB) for 14 weeks. The DEN/PB-administered rats were co-treated with different doses of MFP (50 or 100 mg/kg body weight) by oral gavage for 14 weeks. Basic hepatic function indexes (AST, ALT, ALP, GGT, total bilirubin, and albumin), and hepatic tumor biomarkers (AFP, CEA, and CA19.9), together with histological assessment were performed. Besides, the hepatic apoptosis markers (Bcl-2, Bax, caspase3, and caspase9), inflammation markers (IL-1β, TNF-α, and NF-κB), and mutT homologue gene 1 (MTH1) were examined. Oral gavage of MFP inhibited the elevations of hepatic function indexes and hepatic tumor biomarkers and alleviated pathological changes in hepatic tissue. In addition, the hepatic apoptosis markers, inflammation markers, and the mRNA level of MTH1 were abnormal in DEN/PB group, which were reversed by MFP treatment. In conclusion, MFP is an effective agent that provides chemoprevention against DEN/PB-evoked hepatocarcinogenesis via inhibition of inflammation and induction of apoptosis.